2013
DOI: 10.1097/ajp.0b013e318284e525
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Activity in Response to Procedural Pain in Preterm Infants Born at 28 and 33 Weeks Gestational Age

Abstract: There are technical challenges in recording EEG during procedures, as pain induces motor movements. More research is needed to determine the most sensitive approach to measure EEG signals within the context of pain in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…The majority of these studies (n = 6) have utilised prospective observational and prospective cohort designs to characterise the neuronal electrical response to pain in the infant brain. Of these six studies, two exclusively examined EEG response to pain in full‐term infants , one combined late preterm and term infants in the same sample , and three included both full‐term and preterm infants to examine the development of pain‐specific electrophysiological response across gestational ages . The remaining two studies were randomised controlled trials conducted with full‐term infants to examine the analgesic effect of oral sucrose on pain‐specific EEG response .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies (n = 6) have utilised prospective observational and prospective cohort designs to characterise the neuronal electrical response to pain in the infant brain. Of these six studies, two exclusively examined EEG response to pain in full‐term infants , one combined late preterm and term infants in the same sample , and three included both full‐term and preterm infants to examine the development of pain‐specific electrophysiological response across gestational ages . The remaining two studies were randomised controlled trials conducted with full‐term infants to examine the analgesic effect of oral sucrose on pain‐specific EEG response .…”
Section: Resultsmentioning
confidence: 99%
“…These six studies utilised the same equipment, data sampling ranges and digitisation parameters. The remaining two studies reported minimal information with respect to sampling specifications . All of the included studies reported placing electrodes at midline electrode sites (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, EEG responses and facial reactivity of preterm infants are high in response to procedural pain, however, these measures decrease as the number of skin breaking procedures increases [11,14]. By 3 months of age, these infants show attenuated behavioral responses to acute noxious stimuli (e.g.…”
Section: The Long-term Impact Of Early Life Pain In Humansmentioning
confidence: 99%
“…In response to procedural pain, heart rate and cortisol levels of preterm infants are initially high, but like pain behavior, become blunted as the number of skin breaking procedures increase [11,14]. At 3 months of age, former preterm infants show reductions in both autonomic arousal and cortisol reactivity in response to immunization pain as compared with term peers [15].…”
Section: The Long-term Impact Of Early Life Pain In Humansmentioning
confidence: 99%
“…Recently, researchers have begun to investigate more objective approaches to pain assessment, such as measurement of heart rate variability, skin conductance and cortisol as a biomarker of stress [23, 25]. To better understand and assess neonatal pain responses at cortical level, newer brain-oriented techniques, such as electroencephalography (EEG) [28, 29] and functional magnetic resonance imaging (fMRI) [30, 31], are used [11, 3234]. However, for systematic clinical pain assessment, exclusively observable indicators need to be considered.…”
Section: Introductionmentioning
confidence: 99%